Problematics of Learning Islamic Religious Education at SMAN 1 Model Tanjung Pura, Langkat District - Hermansyah, Ade; Nasrudin, Endin; Qomariyah, Siti (Eastasouth Institute, 2023)
This research aims to describe Problems in Learning Islamic Religious Education in the Formation of Islamic Character Students of Tanjung Pura State High School, Langkat Regency. This type of research is descriptive with a qualitative approach. Source information for this research is Islamic Religious Education Teachers, School Principals, Students, as well as teachers in other fields of study. Data collection techniques were carried out through interviews, participant observation, and documentation. Technique Data analysis was carried out using the Miles and Huberman model. The findings in this research are about the role of Islamic religious education in schools in forming the character of students. Islamic education (PAI) is one of the most important pillars of character education. Character education will grow well if it starts by embedding religious spirit in children, therefore Islamic Religious Education material (PAI) in schools is one of the supports for character education. Through Islamic Religious Education (PAI) learning, students are taught aqidah as the basis of religion, taught by the Koran and Hadith as his guide to life, taught fiqh as a guide to internal law worship, teach Islamic history as a living example, and teaches morals as a guide to human behavior whether in categories good or bad. Therefore, the main goal of Educational Learning Islamic Religion (PAI) is the formation of personality in students reflected in their behavior and thought patterns in everyday life. In addition, the success of learning Islamic Religious Education (PAI) in One of the schools is also determined by the application of learning methods right.